2012
DOI: 10.1073/pnas.1205592109
|View full text |Cite
|
Sign up to set email alerts
|

Tetrameric assembly of KvLm K + channels with defined numbers of voltage sensors

Abstract: Voltage-gated K þ (Kv) channels are tetrameric assemblies in which each modular subunit consists of a voltage sensor and a pore domain. KvLm, the voltage-gated K þ channel from Listeria monocytogenes, differs from other Kv channels in that its voltage sensor contains only three out of the eight charged residues previously implicated in voltage gating. Here, we ask how many sensors are required to produce a functional Kv channel by investigating heterotetramers comprising combinations of full-length KvLm (FL) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…In line with these experimental measurements, a recent all-atom molecular simulation suggested that full outward movement of S4 in one or two VSDs is insufficient to open the pore [1]. The experiment in the prokaryotic KvLm channels further revealed that three VSDs are required to promote classical voltage-dependent channel opening at depolarizing potentials [16]. In our study, either one or two VSDs are sufficient to open the channels in a voltage-dependent manner.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In line with these experimental measurements, a recent all-atom molecular simulation suggested that full outward movement of S4 in one or two VSDs is insufficient to open the pore [1]. The experiment in the prokaryotic KvLm channels further revealed that three VSDs are required to promote classical voltage-dependent channel opening at depolarizing potentials [16]. In our study, either one or two VSDs are sufficient to open the channels in a voltage-dependent manner.…”
Section: Discussionsupporting
confidence: 71%
“…The work on KvLm channels shed new light on the roles of VSD. However, as it is a prokaryotic channel, the VSD of KvLm contains only three of the eight conserved charged residues known to be deterministic for voltage sensing in eukaryotic Kv channels, which may impede the generalization of these findings to eukaryotic Kv channels [15,16]. To the best of our knowledge, similar protein engineering strategies (physically remove VSDs) have not been successful in eukaryotic Kv channels.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations